Interaction of human leukocytes and Entamoeba histolytica. Killing of virulent amebae by the activated macrophage. - Salata, R A (1985)
Capable effector mechanisms in the human immune response against the cytolytic, protozoan parasite Entamoeba histolytica have not been described. To identify a competent human effector cell, we studied the in vitro interactions of normal human polymorphonuclear neutrophils, peripheral blood mononuclear cells (PBMC), monocytes (MC), and MC-derived macrophages with virulent axenic amebae (strain HMI-IMSS). Amebae killed neutrophils, PBMC, MC, and MC-derived macrophages (P less than 0.001), without loss of parasite viability. The addition of heat-inactivated immune serum did not enable leukocytes to kill amebae, nor did it protect these host cells from amebae. MC-derived macrophages, activated with lymphokine elicited by the mitogens conconavalin A, phytohemagglutinin, or an amebic soluble protein preparation (strain HK9), killed 55% of amebae by 3 h in a trypan blue exclusion assay (P less than 0.001); during this time, 40% of the activated macrophages died. Lysis of amebae was confirmed using 111Indium oxine radiolabeled parasites and was antibody independent. Macrophage death appeared to be due to the deleterious effect of lysed amebae rather than the contact-dependent effector mechanisms of E. histolytica. Adherence between activated macrophages and amebae was greater than that between other leukocytes and amebae (P less than 0.001). Microscopic observations, kinetic analysis of the killing of amebae by activated macrophages, and suspension of amebae with adherent activated macrophages in a 10% dextran solution indicated that contact by activated macrophages was necessary to initiate the killing of amebae. Catalase but not superoxide dismutase inhibited the amebicidal capacity of activated macrophages (P less than 0.001). However, activated macrophages from an individual with chronic granulomatous disease were able to kill amebae, but not as effectively as normal cells (P less than 0.01). In summary, activated MC-derived macrophages killed virulent E. histolytica trophozoites through a contact-dependent, antibody-independent mechanism involving oxidative-dependent and -independent processes.